Deliberative Learning in Elementary Civic Education: Strengthen Students’ Communication Skills from a Vocational Perspective - Alya Rahmadiyani; Dinie Anggraeni Dewi; Agil Nanggala; Roel V. Avilla (Jurnal Paedagogy, 2026)
This study aims to formulate a deliberation-based Civic Education learning model from a vocational civic perspective to strengthen elementary school students’ communication skills. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews with Civic Education experts and classroom teachers at SDN 268 Panyileukan, classroom observations of the deliberative learning process, and document analysis. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing and verification. The findings indicate that the integration of deliberative practices with vocational civic education enhances students’ assertive and persuasive communication skills, active listening abilities, and collaborative competencies. In addition, the model fosters key character values, including tolerance, empathy, social discipline, and cooperation. This deliberation-based learning model is expected to serve as both a practical and theoretical reference for teachers, curriculum developers, and policymakers in implementing contextual and participatory Civic Education that emphasizes character development and 21st-century skills.